Active control of radiation beaming from Tamm nanostructures by optical microscopy. (28th March 2018) - Feng, Fu; Symonds, Clémentine; Schwob, Catherine; Bellessa, Joël; Maître, Agnès; Hugonin, Jean-Paul; Coolen, Laurent
Abstract: Active control of the radiation orientation (beaming) of a metallic antenna has been reported by various methods, where the antenna excitation position was tuned with a typical 50 nm precision by a near-field tip or an electron-beam. Here we use optical microscopy to excite and analyze the fluorescence of a layer of nanocrystals embedded in an optical Tamm state nanostructure (metallic disk on top of a Bragg mirror). We show that the radiation pattern can be controlled by changing the excitation spot on the disk with only micrometer precision, in a manner which can be well described by numerical simulations. A simplified analytical model suggests that the propagation length of the in-plane confined optical modes is a key parameter for beaming control.